Analisis Kepastian Hukum Terhadap Standar Keamanan Sertifikat Elektronik Dalam Kepemilikan Tanah - Ni Komang Arinda Sastra Pramesti; Made Mulyawan Subawa; Deli Bunga Saravistha (Kertha Wicaksana, 2026)
The digital transformation in land services through the implementation of electronic certificates in Indonesia constitutes a significant step in modernizing bureaucracy and enhancing legal certainty regarding land ownership rights. This study aims to analyze the legal certainty concerning the security standards of electronic certificates within the context of protecting land rights and landowners' personal data protection. The research employs a normative legal method with statutory and case study approaches. The findings indicate that the issuance of electronic certificates has a strong legal basis through Ministerial Regulation of ATR/BPN No. 1 of 2021, Law No. 11 of 2008 on Electronic Information and Transactions, and Law No. 5 of 1960 on the Basic Agrarian Law (UUPA). Electronic certificates offer various benefits, such as administrative efficiency, transparency, and service accessibility. However, public concerns have arisen regarding data security and the risk of forgery, highlighting the importance of integration with Law No. 27 of 2022 on Personal Data Protection. Protective measures are implemented through the use of certified electronic signatures, validation QR codes, and a layered security system adopting public key cryptography. This system provides legal protection to landowners against misuse and certificate forgery. This study concludes that while the electronic certificate system promises enhanced legal certainty, regulatory strengthening, IT system security improvements, and public education are still required to build public trust in the digital land administration system.